Induction in guinea-pigs of airway hyperreactivity and decreased lung beta-adrenoceptor number by 15-hydroperoxy-arachidonic acid. - Folkerts, G. (Nature Publishing Group, 1983)
Administration to guinea-pigs of 15-hydroperoxy-arachidonic acid (0.2 mg kg-1 i.p.) caused a 20% reduction of lung beta-adrenoceptor number. Furthermore, in vivo, a hyperreactivity of the airways to nebulized histamine was observed. In contrast, administration of 15-hydroxy-arachidonic acid (0.2 mg kg-1 i.p.) did not cause a significant change in either of these parameters.